Fumonisins in maize and gluten meal analysed in Argentinean wet milling industrial plants by ELISA compared with HPLC-FLD method - Coronel, María Bernarda (2016)
Fumonisins are frequent contaminants of maize. Wet milling industrial plants in Argentina control not only maize, but the fractions of the process. The performance of two ELISA test kits (G and K) from different brands used in six plants to determine fumonisins in maize and gluten meal was evaluated by comparison with HPLC results. ELISA determinations in maize (n = 43) and gluten meal (n = 45) were carried out in the plants and HPLC analysis was done in our laboratory. No significant differences (P > 0.05) were found in most cases when fumonisins concentrations were within the ELISA quantification range. Thus, ELISA tests performed according to validated protocols are useful tools for screening purposes, but levels nearest the settled limits for rejection of lots should be confirmed by HPLC because of the high relative standard deviation of ELISA analyses. The contamination pattern of fumonisins in gluten meal was different from that of maize, with higher levels of FB2 than those of FB1.